SPE Reservoir Simulation Symposium 2009
DOI: 10.2118/119132-ms
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Mimetic Solvers for Efficient Streamline Simulation of Fractured Reservoirs

Abstract: Advances in reservoir characterization and modeling have given the industry improved ability to build detailed geological models of petroleum reservoirs. These models are characterized by complex shapes and structures with discontinuous material properties that span many orders of magnitude. Models that represent fractures explicitly as volumetric objects pose a particular challenge to standard simulation technology with regard to accuracy and computational efficiency. We present a new simulation approach base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…By far, the most well-developed method in terms of geomodel complexity is the multiscale mixed finite-element method, which is posed in terms of degrees-of-freedom associated with the fluxes between neighboring coarse blocks. The method only requires a primal coarse partition and can hence easily be formulated on structured, stratigraphic grids as well as fullyunstructured, polyhedral grids (Aarnes et al 2006(Aarnes et al , 2008Krogstad et al 2009;Natvig et al 2011;Alpak et al 2012;Lie et al 2014). An extended approach based on proper orthogonal decompositions (POD) was suggested by Krogstad (2011) for problems in which one wants to investigate new cases that represent minor changes to scenarios that have already been simulated by a multiphase simulation.…”
Section: Multiscale Pressure Solversmentioning
confidence: 99%
See 1 more Smart Citation
“…By far, the most well-developed method in terms of geomodel complexity is the multiscale mixed finite-element method, which is posed in terms of degrees-of-freedom associated with the fluxes between neighboring coarse blocks. The method only requires a primal coarse partition and can hence easily be formulated on structured, stratigraphic grids as well as fullyunstructured, polyhedral grids (Aarnes et al 2006(Aarnes et al , 2008Krogstad et al 2009;Natvig et al 2011;Alpak et al 2012;Lie et al 2014). An extended approach based on proper orthogonal decompositions (POD) was suggested by Krogstad (2011) for problems in which one wants to investigate new cases that represent minor changes to scenarios that have already been simulated by a multiphase simulation.…”
Section: Multiscale Pressure Solversmentioning
confidence: 99%
“…This makes multiscale simulation a better tool for characterizing volumetric sweep and locating bypassed and immobile oil compared with traditional upscaling, which always implies a loss of information when homogenizing fine-scale structures. Previous research has shown that multiscale and streamline methods constitute a powerful and computationally efficient combination (Aarnes et al 2005;Stenerud et al 2008;Natvig et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Physical properties inside fractures and their length scales can be very di↵erent from those of the surrounding rock, adding significantly to the computational challenges, specially once realistic length scales and complex fracture network maps are considered. As a result, a variety of modelling approaches and numerical methods for di↵erent types of fractured reservoirs have been proposed [32][33][34][35][36][37][38][39][40][41][42][43][43][44][45][46][47]. Among them, the embedded fracture modelling approach [1, 37-39, 48, 49] benefits from independent grids for fracture and matrix, a promising approach for naturally fractured reservoirs and also for cases with dynamic fracture creations and closure of, e.g., geothermal systems.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is highly important to develop e cient multiscale methods for fractured formations. Early attempts at developing multiscale methods for fractured media were based on a mixed finite-element formulation in which high-conductive fractures were either represented explicitly as volumetric objects [40] or the fracture-matrix interaction was modelled by the Stokes-Brinkmann equations [41,50]. Within the MSFV framework, Hajibeygi et al [1] developed the first multiscale method for fractured porous media, in which additional fracture basis functions were introduced to map each fracture network into one coarse-scale degree of freedom (DOF).…”
Section: Introductionmentioning
confidence: 99%
“…If the transport is to be computed on the same coarse grid as used in the multiscale flow solver, the best choice is to use a standard implicit finitevolume method with the coarse-scale fluxes computed by the multiscale solver. To solve the transport without upscaling-using the fine-scale, approximate fluxes-the best choice is probably a streamline method, e.g., as described in [1,20], or one can use similar operatorsplitting techniques to develop highly-efficient finite-volume solvers [18,19] that use flow information to obtain an optimal ordering of the nonlinear discrete transport equations so that these can be solved in a cell-by-cell or block-by-block fashion. This gives local control over the (computationally expensive) nonlinear iterations and can significantly reduce the computational cost compared with standard (implicit) finite-volume methods.…”
Section: Introductionmentioning
confidence: 99%